(Acetonitrile-κN)aqua[N,N′-bis(pyridin-2-ylmethyl)ethane-1,2-diamine-κ4N,N′,N′′,N′′′]zinc(II) perchlorate - Ugochukwu Okeke; Yilma Gultneh; Ray J. Butcher (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The structure of the title compound, [Zn(C14H18N4)(C2H3N)(H2O)](ClO4)2, contains a six-coordinate cation consisting of the tetradentate bispicen ligand, coordinated water, and coordinated acetonitrile, with the latter two ligands adopting a cis configuration. There are two formula units in the asymmetric unit. Both cations show almost identical structural features with the bispicen ligand adopting the more common cis-β conformation. One of the four perchlorate anions is disordered over two positions, with occupancies of 0.9090 (15) and 0.0910 (15). There is extensive inter-ionic hydrogen bonding between the perchlorate anions and O—H and N—H groups in the cations, including a bifurcated hydrogen bond between an N—H group and two O atoms of one perchlorate anion. As a result of this extended hydrogen-bond network, the ions are linked into a complex three-dimensional array.